2020
DOI: 10.37689/acta-ape/2020ao0107
|View full text |Cite
|
Sign up to set email alerts
|

Infecção e óbitos de profissionais da saúde por COVID-19: revisão sistemática

Abstract: Infecção e óbitos de profi ssionais da saúde por COVID-19: revisão sistemática Infection and death in healthcare workers due to COVID-19: a systematic review Infección y muerte de profesionales de la salud por COVID-19: revisión sistemática

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 28 publications
0
11
0
19
Order By: Relevance
“…In this critical time, the role of leadership cannot be ignored (Billings et al, 2020;Sant'Ana et al, 2020;Zhao et al, 2020a). While studies have shown that transformational leadership, inclusive leadership and servant leadership seems to be a suitable leadership style for managing employees working in education sector during this pandemic, there is no evidence on the effectiveness of these leadership styles in hospitals settings and occupational safety offered by these leadership styles (Azizaha et al, 2020;Fournier et al, 2020;Zhao et al, 2020b;Antonopoulou et al, 2021;Piorun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this critical time, the role of leadership cannot be ignored (Billings et al, 2020;Sant'Ana et al, 2020;Zhao et al, 2020a). While studies have shown that transformational leadership, inclusive leadership and servant leadership seems to be a suitable leadership style for managing employees working in education sector during this pandemic, there is no evidence on the effectiveness of these leadership styles in hospitals settings and occupational safety offered by these leadership styles (Azizaha et al, 2020;Fournier et al, 2020;Zhao et al, 2020b;Antonopoulou et al, 2021;Piorun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…O fato dos domínios mais afetados nos profissionais serem o meio ambiente e o psicológico ratificam dados encontrados em revisão sistemática que aponta um alto número de profissionais infectados, bem como a sobrecarga de trabalho e o medo de sua infecção e de seu círculo próximo como fatores de risco para a infecção e, em alguns casos, consequente óbito de profissionais de saúde (17) .…”
Section: Resultsunclassified
“…Ademais, esses trabalhadores em saúde são mais expostos a riscos laborais porque permanecem mais tempo na assistência direta aos pacientes (Sant'Ana et al, 2020;Souza e Souza, 2020;Tavares e Souza et al, 2015), consequentemente, maior exposição ao vírus (Felli, 2012). Estudos apontam que os trabalhadores de enfermagem realizam uma jornada semanal de trabalho maior que 44 horas semanais, e que a dupla jornada de trabalho se faz necessária devido aos baixos salários que são insuficientes para o sustento da família (Pafaro & Martino, 2004).…”
Section: Discussionunclassified
“…Nesse mesmo sentido, revisão sistemática destaca como fatores de risco para infecção e óbitos de profissionais da saúde pela COVID-19, o contato próximo com pacientes e/ou colegas de trabalho potencialmente contaminados e procedimentos com risco de geração de aerossol (Sant'Ana et al, 2020). Os achados deste estudo corroboram essa afirmativa, pois a grande maioria dos enfermeiros e técnicos/auxiliares de enfermagem tinham como setor de trabalho uma área crítica (ANVISA, 2010).…”
Section: Discussionunclassified